Analisis Prestasi Pendidikan Anak Penerima Bantuan Program Keluarga Harapan Di Kecamatan Peranap Kabupaten Indragiri Hulu - Andrel Rosevelt; B. Isyandi; Sri Endang Kornita (Jurnal Niara, 2022)
This study aims to analyze the educational achievements of children who receive assistance from the Hope Family Program in the Peranap District, Indragiri Hulu Regency and to find out the factors that influence it. This research is a primary research that collects data using a research questionnaire. The total population of the study was all families receiving the family hope program assistance in the role of the role of the Indragiri Hulu Regency, namely as many as 446 families, then based on the Slovin formula with a level of 10%, the total sample size was 82 respondents in which the respondents were divided into families who have selected school children, namely the highest PKH recipient child education. The analytical method used is descriptive quantitative using multiple linear regression analysis. Based on the results of the study, it is known that the Family Hope Program (PKH) assistance has a significant positive effect on the educational achievement of children receiving the Hope Family Program (PKH) in Peranap District, Indragiri Hulu Regency. The level of attendance of children has a significant positive effect on the educational achievement of children receiving the Hope Family Program (PKH) in the Peranap District, Indragiri Hulu Regency. Parents' income has a significant positive effect on the educational achievement of children receiving the Hope Family Program (PKH) in the Peranap District, Indragiri Hulu Regency. If the parents' income increases, it will increase the educational achievement of children who receive the Hope Family Program (PKH) in Peranap District, Indragiri Hulu Regency. And the level of parental education has a significant positive effect on the educational achievement of children receiving the Hope Family Program (PKH) in the Peranap District, Indragiri Hulu Regency.